2016
DOI: 10.1002/dev.21452
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in the temporal parameters of sensory preconditioning during infancy

Abstract: Sensory preconditioning (SPC) is a form of latent learning in which preexposure to co-occurring neutral stimuli (S1-S2) permits subsequent learning to be transferred from one stimulus (S1) to the other (S2). We examined whether human infants exhibit developmental transitions in the temporal parameters of SPC by manipulating the preexposure regimen. Infants received simultaneous or sequential preexposure to puppets S1 and S2 (Days 1–2); saw target actions modeled on S1 (Day 3); and were tested for deferred imit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…In SPC, CR arises in direct response to sensing NS2, which is preconditioned to CS (formerly NS1) in the sensory system, which triggers CR in anticipation of US. According to the recent research by Cuevas and Giles [134], the SPC mechanism was observed in human infants' anticipatory behavior and latent learning capabilities.…”
Section: ) Anticipatory Behaviormentioning
confidence: 98%
“…In SPC, CR arises in direct response to sensing NS2, which is preconditioned to CS (formerly NS1) in the sensory system, which triggers CR in anticipation of US. According to the recent research by Cuevas and Giles [134], the SPC mechanism was observed in human infants' anticipatory behavior and latent learning capabilities.…”
Section: ) Anticipatory Behaviormentioning
confidence: 98%
“…Interestingly, in both the SPC work described above and this memory binding paradigm, 12‐month‐olds failed to exhibit memory when co‐occurring stimuli were presented simultaneously during encoding. Thus, the superior relational memory performance of younger infants might also be related to overlapping changes in the demands of the infant's ecological niche (e.g., selective attention, independent locomotion) as noted in the context of SPC (Cuevas & Giles, ). Evidence of relational memory with sequential presentations of face–scene stimuli at 12, but not 6 months, as seen in SPC research, would support this notion.…”
Section: Functional Analyses Of Infant Memorymentioning
confidence: 99%
“…Likewise, the frequency and timing of reminders or memory retrievals affect not only long-term memory duration, but also both the speed with which a forgotten memory is retrieved and the minimum duration of an effective reminder (Barr, Rovee-Collier, & Campanella, 2005;Bearce & Rovee-Collier, 2006;Hayne, 1990;Hayne, Gross, Hildreth, & Rovee-Collier, 2000). The hyperspecificity of early memory is also "overcome" by varied experience with focal cues or environmental surrounds, which can occur before or during initial learning or subsequent reminding after initial forgetting (Amabile & Rovee-Collier, 1991;Cuevas & Giles, 2016;Hitchcock & Rovee-Collier, 1996).…”
Section: Varied Experiencementioning
confidence: 99%
See 2 more Smart Citations